Analysis Of The Cooperation Results Sharing System Between Palm Oil Plantation Workers And Garden Owners According To An Islamic Economic Perspective, Case Study In Sei District. Asahan District Chief - Siti Jihan; Tuti Anggraini; Muhammad Latif Ilhamy nasution (UNIVERSITAS PAKUAN, 2024)
This study aims to analyze the profit sharing system in cooperation between workers in oil palm plantations and plantation owners, taking into account the perspective of Islamic economics. The research method used is field research that uses descriptive qualitative research methods. Production sharing cooperation agreements between labor and oil palm plantation owners are common practices that regulate work relationships and the distribution of production results. Production sharing cooperation agreements are a common practice that regulates labor relations and the distribution of production results in the palm oil industry in Sei Kepayang. The agreement is an agreement between the landowner and the land manager. Where the land manager provides halan and equipment while the land manager works on the land that is entrusted properly. In this case, the landowner is responsible for bearing losses if there is damaged equipment and other mistakes that are not caused by the negligence of the land manager. The weakness in the profit-sharing system in Sei Kepayang Sub-district is that there is no recording in the profit-sharing cooperation carried out. All agreements are only carried out in the form of a written agreement, namely an agreement in the mouth or only verbally, so that the agreement has weaknesses in terms of legal force. In the implementation of cooperation between migrant workers and plantation owners in Sei Kepayang, the view of Islamic economics refers to the main principles contained in Islamic law, namely the principle of balance, the principle of divinity, the principle of morals, and the principle of balance. This aims to ensure that this cooperation aims to improve the level of welfare for all parties involved, and not only to obtain large profits.